2015
DOI: 10.1007/s00477-015-1021-9
|View full text |Cite
|
Sign up to set email alerts
|

Flood susceptibility analysis and its verification using a novel ensemble support vector machine and frequency ratio method

Abstract: Flood is one of the most commonly occurred natural hazards worldwide. Severe flood occurrences in Kelantan, Malaysia cause damage to both life and property every year. Due to the huge losses in this area, development of appropriate flood modeling is required for the government. Remote sensing and geographic information system techniques can support overall flood management as they can produce rapid data collection and analysis for hydrological studies. The existing models for flood mapping have some weak point… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
161
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 377 publications
(166 citation statements)
references
References 74 publications
3
161
0
2
Order By: Relevance
“…In order to generate a model for evaluating the hazard susceptibility, a series of conditioning parameters must be defined [5,42,43]. Various thematic data layers representing flash flooding hazard conditioning parameters, such as elevation, slope, curvature, land use, geology, soil texture, subsidence risk area, stream power index (SPI), topographic wetness index (TWI), and short-term heavy rain, were derived.…”
Section: Conditioning Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to generate a model for evaluating the hazard susceptibility, a series of conditioning parameters must be defined [5,42,43]. Various thematic data layers representing flash flooding hazard conditioning parameters, such as elevation, slope, curvature, land use, geology, soil texture, subsidence risk area, stream power index (SPI), topographic wetness index (TWI), and short-term heavy rain, were derived.…”
Section: Conditioning Parametersmentioning
confidence: 99%
“…Quantifying the extent and coverage of damage due to flooding is extremely difficult [4]. Floods occur at different intervals and with varying durations [5]. Therefore, assessment and mitigation of flash floods cannot be overlooked.…”
Section: Introductionmentioning
confidence: 99%
“…Clearly, in an urbanized area, the buildings, the drainage system and the road infrastructure will also contribute to flood water routing and will help determine the actual flood extents observed. In such cases, the TWI will be a less precise means of delineating flood-prone areas, and additional variables should be considered (Tehrany et al 2015;Jafarzadegan and Merwade 2017). This might entail fitting multivariate probabilistic models and using simulation-based approaches, such as MarkovChain Monte Carlo Simulation or Machine Learning procedures, to carry out the Bayesian inference.…”
Section: Discussionmentioning
confidence: 99%
“…Kazakis et al (2015) introduced a multicriteria index to assess flood hazard areas that relies on GIS and analytical hierarchy processes (AHPs); in this methodology, the relative importance of each flood-influencing factor for the occurrence and severity of flood was determined via AHP. More recently, support-vector-machine-based flood susceptibility analysis approaches have been proposed by Tehrany et al (2015a, b); the research finding is that SVM is more accurate than other benchmark models, including the decision tree classifier and the conventional frequency ratio model. Mukerji et al (2009) constructed flood forecasting models based on an adaptive neuro-fuzzy interference system (ANFIS), genetic algorithm optimized ANFIS; experiments demonstrated that ANFIS attained the most desirable accuracy.…”
Section: A Review Of Related Work On Flood Susceptibility Predictionmentioning
confidence: 99%